Cybersecurity and Innovation Risk Management: Organizational Responses in the Digital Era - Noviany, Henny; Prasetyo, Karno Ganjar (Novatio : Journal of Management Technology and Innovation, 2025)
The rapid pace of digital transformation has reshaped healthcare, finance, and energy sectors, creating opportunities for innovation while amplifying vulnerabilities to cyber threats. This narrative review synthesizes organizational responses to cybersecurity and innovation risk management across global contexts. Literature was systematically collected from Scopus, Web of Science, PubMed, and Google Scholar using defined keywords and inclusion criteria, with thematic synthesis guided by review standards. Four central themes emerged: (1) the effectiveness of secure access and identity management in protecting sensitive data, (2) the integration of artificial intelligence and blockchain in predictive modeling and threat detection, (3) measurable improvements in resilience through advanced technological adoption, and (4) the influence of systemic and structural factors, including governance frameworks and international collaboration. Evidence highlights disparities between developed and developing regions, where resource and infrastructure limitations hinder adoption. The discussion links findings with resilience theory while noting limitations such as the neglect of SMEs, dominance of Western perspectives, and reliance on secondary data. Policy implications emphasize capacity-building, harmonized frameworks, and innovation-driven cultures. Comprehensive, collaborative, and context-sensitive approaches are essential for advancing cybersecurity resilience in the digital era.